1998
DOI: 10.1161/01.str.29.5.924
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical Treatment on the Outcome of Patients After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-The rationale behind early aneurysm surgery in patients with subarachnoid hemorrhage (SAH) is the prevention of rebleeding as early as possible after SAH. In addition, by clipping the aneurysm as early as possible, one can apply treatment for cerebral ischemia more vigorously (induced hypertension) without the risk of rebleeding. Hypervolemic hemodilution is now a well-accepted treatment for delayed cerebral ischemia. We compared the prospectively collected clinical data and outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 53 publications
1
47
0
Order By: Relevance
“…here have been many reports investigating aneurysmal rebleeding, because it is a major cause of death and disability in aneurysmal subarachnoid hemorrhage (SAH) [1][2][3] in addition to the primary bleeding and delayed ischemic deterioration. 4 The cumulative incidence of aneurysmal rebleeding within the first 2 weeks has been estimated to be from 9% to 23%, 3,[5][6][7][8] and the mortality due to rebleeding has been reported to range between 50% and 80%.…”
mentioning
confidence: 99%
“…here have been many reports investigating aneurysmal rebleeding, because it is a major cause of death and disability in aneurysmal subarachnoid hemorrhage (SAH) [1][2][3] in addition to the primary bleeding and delayed ischemic deterioration. 4 The cumulative incidence of aneurysmal rebleeding within the first 2 weeks has been estimated to be from 9% to 23%, 3,[5][6][7][8] and the mortality due to rebleeding has been reported to range between 50% and 80%.…”
mentioning
confidence: 99%
“…A number of studies using both antifibrinolytics and either nicardipine or nimodipine reported decreased rebleeding, no increase in ischemic deficits, and improved outcomes [15,26,28,41,42]. Rebleeding rates ranged from 7% to 13% and mortality ranged from 11% to 12%.…”
Section: Other Non-randomized Clinical Trialsmentioning
confidence: 99%
“…An understanding of this situation has resulted in a move away from fluid restriction in SAH patients to administering sodium containing solutions so that circulating volume is maintained at normal or supra-normal levels. A number of non-randomised trials in which patients were given at least 3 litres per day of saline 0.9% have indicated a decreased rate of delayed cerebral ischaemia and a better overall outcome [63,64]. A recent Cochrane review concluded that there is no sound evidence for or against the use of volume expansion therapy in those patients with aneurysmal subarachnoid haemorrhage [65].…”
Section: Measures Aimed At Decreasing the Risk Of Rebleedingmentioning
confidence: 99%